Impact of progesterone and estradiol treatment before the onset of the breeding period on reproductive performance of Bos indicus beef heifers - Sá Filho, M. F.; Nasser, L. F T; Penteado, L.; Prestes, R.; Marques, M. O.; Freitas, B. G.; Monteiro, B. M.; Ferreira, R. M.; Gimenes, L. U. [UNESP]; Baruselli, P. S. (Elsevier, 2015)
The present aimed to develop a hormonal therapy based on the insertion of a progesterone (P4) insert (PI) during 10 d plus an estradiol injection (E2) at PI removal before the onset of breeding of beef heifers. In Exp. 1, the plasma P4 profile of prepubertal heifers showed that the insertion of a PI or 24 d previously used P4 insert (UPI) sustained plasma P4 above 1ng/mL for at least the first 7 d of the treatment. In Exp. 2 there was no positive effect of additional estradiol benzoate (EB) administered at the insertion of UPI on the proportion of heifers with a corpus luteum (CL/Treated) 30 d after UPI removal [UPI+EB=85.3%a (n=134); EB+UPI+EB=80.8%a (n=125)]; however, both were greater (P<0.0001) than the Control group [60.3%b (n=129)]. In Exp. 3, a positive effect (P=0.01) of UPI treatment and both E2 supplementations [EB and estradiol cypionate (EC); P=0.10] at the UPI removal was observed on CL/Treated [Control=42.5%b (n=94); UPI=58.5%a (n=130); UPI+EB=64.0%a (n=128); UPI+EC=67.2%a (n=128)]. However, greater pregnancy per treated heifer (P/Treated) following artificial insemination (AI) upon estrus detection was achieved when EC was applied [Control=20.2%b; UPI=29.2%ab; UPI+EB=26.6%b; UPI+EC=36.7%a]. In Exp. 4, the treatment prior to the timed AI (TAI) tended to improve pregnancy per TAI [P/AI; Control 43.6% (n=298) vs. UPI+EC 51.9% (n=342); P=0.08], but increased P/Treated [26.5% vs. 43.3%; P<0.001]. Thus, UPI+EC treatment were efficient in increasing the CL/Treated, tended to improve the P/AI and consequently enhanced P/Treated of zebu beef heifers.
Keywords: Anestrous; Bovine; Puberty; Reproduction; Reproductive efficiency